Farelo do resíduo de tucumã (Astrocaryum aculeatum) em substituição ao milho na alimentação de poedeiras comerciais - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
The present study aimed to evaluate the tucumã meal as substitute of corn in diets for commercial laying hens. The experimental period during 84 days, divided into four cycles of 21 days each. A total of 180 laying hens of the Hisex White lineage were used. The experimental method completely randomized with the treatments constituted by six levels of tucumã meal replacing the corn (0, 20, 40, 60, 80 and 100%) and five replicates of six birds each. Were evaluated the performance, egg quality and economical viability. Data collected were subjected to polynomial regression at 5% of significance. Differences (P<0.05) were observed in performance, egg quality and economical analysis. The treatment with 100% of substitution showed worse results. The results of other levels didn't differ among themselves. In the sensory analysis the treatments with greater inclusion of tucumã presented eggs with more attractive taste and pigmentation of the yolk, besides the characteristic flavor of the fruit of A. aculeatum. In summary, it's possible used up to 60% of tucumã meal in substitution of corn in diets for laying hens, without negative affect the performance and egg quality, showed good economical viability.
Keywords: Alimento alternativo; Avicultura; Viabilidade econômica; Alternative food; Poultry science; CIENCIAS AGRARIAS: ZOOTECNIA